Stress-related growth of HIV/AIDS patients: role of religion and self-esteem in mitigating perceived discrimination - Fauzia Maqsood; Ummel Baneen; Sidra Maqsood (Journal of the Pakistan Medical Association, 2021)
Objectives: Objectives of present research were to i) examine association between levels of religiosity, self-esteem, perceived discrimination and stress related growth among HIV/AIDS Patients and ii) find out the mediating effect of self-esteem on perceived discrimination and stress related growth among HIV/AIDS Patients. Methods: It was a cross sectional study. The respondents were registered in VCCT (Voluntary Confidential Counseling & testing) center at Civil Hospital of Jalal Pur Jattan, Gujrat. Total sample of 247 patients was selected on the basis of two stage stratified simple random sampling technique. After taking verbal consent from respondents, data was collected from HIV/AIDS patients by using a structured questionnaire. Analysis was performed by using SPSS version 21 Results: Results of descriptive analysis showed that majority of respondents belonged to age group 29-37 (39.5%). Educational attainment of majority of the respondents was 6-11 years (38.3%), whereas, 27.4% of the respondents had monthly household income between Rs.10001-20000. Conclusion: Results of correlation and regression analysis showed that level of religiosity and self-esteem had significant effects in reducing perceived discrimination among HIV/AIDS patients. The reduced perceived discrimination further assisted in improving the stress related growth among respondents. Based on the findings it is suggested that special programs for accelerating stress related growth among HIV/AIDS patients by enhancing their self-esteem may be arranged and most importantly this issue may be raised in the religious sessions to discuss it and for removing the related stigma. It would be helpful for HIV/AIDS patients to cope with the disease. Continuous...